On the 3j symmetries - Newmarch, J.D. (AIP Publishing, 1983)
The symmetry properties of the 3jm tensor for any finite or compact linear group are discussed using a wreath product construction. This is shown to provide a complete group theoretic explanation for all symmetry properties whether "essential" or "arbitrary." The link with the similar-but distinct-method of inner plethysms is considered.